Система біблійних образів у прозі Григорія Сковороди - Александрович, Т. (Літературознавчі обрії. Праці молодих учених, 2010)
The article focuses on the issue of biblical characters in the prose of Grygoriy Skovoroda. The key characters in the God’s book (Jesus Christ, Moses, Paul and Lot) and their interpretation by Ukrainian writer are analyzed. A series of female biblical characters that help the author to show different interpretations of perception of given characters is represented. The article affirms that the key feature of Grygoriy Skovoroda’s works is reinterpreting the characters of the God’s book and giving them another meaning not just to show his own ideas but to show ordinary life truths.